Anterior opercular syndrome induced by Epstein–Barr virus encephalitis. Issue 1 (2nd January 2016) - Matsushima, Takashi; Nishioka, Kenya; Tanaka, Ryota; Yokoyama, Kazumasa; Hattori, Nobutaka
Abstract : We report a 19-year-old female presenting with fever, drooling, anarthria, and voluntary facial movement disruption, characteristic of anterior opercular syndrome (AOS). Serological examination revealed Epstein–Barr virus (EBV) infection following acute encephalitis with severe ataxia. A single-photon emission computerized tomography (SPECT) examination indicated hypoperfusion in the left perisylvian region, bilateral thalamus, occipital lobe, and cerebellum. This is the first report of AOS related to EBV encephalitis. SPECT was a useful method for detecting the damaged region of the operculum. In addition, AOS is a clinically distinct entity that may help us understand the mechanisms of language circuits within the operculum.